Abdominal Circumference Ratio for the Diagnosis of Intertwin Birth Weight Discordance - Simoes, T (2011)
OBJECTIVES: We assessed the accuracy of predicting severe twin birth weight discordance (>25%) using the estimated fetal weights (EFW) and abdominal circumference (AC) ratio. METHOD: A cohort of twin gestations underwent ultrasound examinations within two weeks from birth. We focused on the accuracy of EFW and on the diagnosis of severe birth weight discordance by the difference in EFWs and the AC ratio. RESULTS: The 661 eligible twin pairs included 51 (7.7%) severely discordant pairs. The accuracy of an EFW to predict the actual birth weight was quite poor, with an acceptable specificity (96.4%), but low sensitivity (28.6-40.5%), to detect severely discordant pairs, whereas an AC ratio of 1.3 detected these discordant pairs with sensitivity and specificity of 97.3-100% and 99.6-99.7%, respectively. CONCLUSION: By comparing EFWs, 59.5-71.4% of discordant pairs >25% are missed, whereas an AC ratio >1.3 would identify almost all cases.